Fenomena budaya carok sebagai nilai kehormatan di Madura - Ramadhani, Ema; Hasaniyah, Nur (Maliki Interdisciplinary Journal, 2025)
Carok in Madura reflects the value of honor (karrapah), which is central to the social identity of its people. This tradition is understood as a symbol of courage to uphold dignity, even though the Madurese prioritize deliberation and reconciliation in resolving conflicts. This study employs content analysis of articles and books to examine the meaning of carok and the role of cultural values in conflict resolution. The findings highlight the importance of strengthening the tradition of deliberation as a more harmonious solution, replacing violence while preserving Madurese cultural values in the face of modernization. These cultural values ​​need to be maintained and developed without maintaining violent elements such as carok. Conflict resolution through deliberation and mutual forgiveness must be prioritized as a more constructive and harmonious method.